PENGEMBANGAN BAHAN AJAR IPS BERBASIS KERAGAMAN BUDAYA BATIK JENOGOROAN UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA - Hidayah, Siti Nurul (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
Abstract This study aims to improve critical thinking through the development of social sciences teaching material toward cultural diversity batik jenogoroan in students class VII SMPN 2 Bojonegoro. The research was conducted in three stages following the draft Borg and Gall, that is the preliminary studies aimed, the stage of product designing teaching materials students with the module, and continued with the testing stage or stages of implementation in the classroom design was one group pretest-posttest design. Data from the research results obtained as follows: (1) the feasibility of module based cultural diversity batik jenogoroan worthy used through 3 expert validation test, the feasibility of module seen from three components: content, presentation, and language. The results of the validation of third validator namely: the average score of the content component 3.53, 3.40 linguistic components, and presentation components of 3.55. All three scores indicate good category/feasible, which means module based cultural diversity-based batik jenogoroan can be used with minimal revision. (2) the effectiveness of module toward cultural diversity batik jenogoroan can enhance students' critical thinking can be seen from the test results between the pre-test and post-test, the results showed that the average score pre test 72.13%, while the average score of post test 80.35%. The results of the pre-test to post-tets increased 8.22. Based on the analysis, it can be concluded that based teaching materials cultural diversity batik jenogoroan can effectively improve critical thinking students' VII classes in social studies, especially on the matter of cultural diversity when seen from the test results that have increased. Keywords: Teaching Materials, Cultural Diversity, Batik Jenogoroan, Critical Thinking